Radiological analysis of the relationship between occlusal tooth wear and mandibular alveolar bone density and height - Erkan Özcan; Fidan Alakus Sabuncuoglu (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to examine the relationship between occlusal tooth wear and mandibular alveolar bone density (ABD) and alveolar bone height (ABH) using computer-assisted densitometric image analysis (CADIA) program. Materials and Methods: The study was comprised of 134 mandibular first molar teeth in 90 patients with various degrees of occlusal tooth wear. The degree of tooth wear was classified according to the tooth wear index (TWI). Periodontal examinations were performed on all patients and included plaque index, gingival index, probing depth, and clinical attachment loss measurements. ABD and ABH were measured from intraoral digital periapical radiographs and analyzed using CADIA. Results: No increases in ABD were observed between TWI 0 and TWI 1 or between TWI 0 and TWI 2 (P > 0.05). However, increases in ABD were observed between TWI 0 and TWI 3 (P < 0.01), TWI 1 and TWI 3 (P < 0.01), TWI 1 and TWI 2 (P < 0.05) and TWI 2 and TWI 3 (P < 0.05). In addition, ABH was found to increase with increase in wear, with the exception of the interval between TWI 0 and TWI 1. Conclusions: Occlusal tooth wear does not result in any radiologically identifiable changes in the alveolar bone during the initial stages of wear; however, significant increases in both ABD and ABH may be observed as tooth wear progresses.